Symbolic Interaction of the Chinese Community in Chengbeng (Sembahyang Kubur) Cultural Rituals (Study on the Ethnic Society of China Belinyu Bangka Belitung) - Yang Gusti Feriyanti; Rizky Oktarina Costa; Muhammad Gunawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to know how the symbolic interaction of Cheng Beng procession for Chinese ethnicity in northern Belinyu Bangka Belitung island Province. Cheng Beng is an annual cultural ritual with cultural and symbolic meanings carried out from generation to generation. The acculturation process, social changes in the Chinese society do not change the importance of Cheng Beng that have moral values, such as obedience and respect for ancestors and parents who have died. This research used a descriptive qualitative approach and was supported with research instruments in the form of an unstructured interview, observation, participants, and literature study. The selected informants were ten people consisting of 5 young generations and five older generations of Chinese ethnicity. The research results show that symbolic interaction in Cheng Beng cultural ritual, besides having ethical values, such as obedience and way of repaying parents or ancestors who have died, also creates harmony and local wisdom between the Chinese and Malay ethnicities. This study concludes that Cheng Beng's cultural ritual creates social identity formation, acculturation, and balance in the Chinese and Malay ethnic communities.